Harga energi dan ketahanan ekonomi masyarakat menengah ke bawah - Suharto Suharto (Universitas Islam Indonesia, 1998)
The determination of price of energy in Indonesia has within complex problems. This article extends the considerations needed in considering the policy. It argues that the strength of middle and lower class economy should be considered in taking the policy.